The Euro-project at risk - Wilhelm Hankel; Andreas Hauskrecht; Bryan Stuart (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2010)
In contrast to Robert Mundell's Optimum Currency Area theory and his recommendation of forming a monetary union, the economic fundamentals of Euro area member countries have not harmonized. The opposite holds: the Euro core countries - most of all Germany, but also the Netherlands and Finland - increased productivity growth while limiting nominal wage growth. However, Mediterranean countries - particularly Greece, but also Spain, Portugal, and Italy - have dramatically lost international competitiveness. Although the overall balance of payments for the Euro area at large is almost balanced, internal disequilibria are skyrocketing and default risk premiums and tensions within the Euro area are rising, thus jeopardizing the stability of the monetary union. The findings confirm that a common currency without fiscal union is inherently unstable. The international financial and economic crisis has merely triggered events which highlight this instability. The paper discusses three possible scenarios for the future of the Euro: a laissez faire approach, a bailout, and finally an exit strategy for the Mediterranean countries, or an organized exit by a group of core countries led by Germany, forming their own smaller monetary union.
Keywords: E42; E5; E63; F15; F33; F34; 330; Optimum currency areas; monetary union; risk spreads; central banking; exchange rates; fiscal policy